The role of phosphorylation in the function of RBR-interacting phosphatase subunit - Yu, Ping (Acta Biologica Szegediensis, 2011)
Protein phosphatase 2A (PP2A) is a serine/threonine-specific phosphatase comprising a catalytic subunit(C), a scaffolding subunit (A), and a regulatory subunit (B). The B subunits are believed to be responsible for substrate specificity and localization of the PP2A complex. In plants, three families of B subunits exist, i.e. B (B55), B’, and B”. Here, we focused on one of the B” regulatory subunit of rice. In yeast two hybrid analyses, the B” regulatory subunit shows strong interaction with the rice retinoblastoma-related protein 1 (OsRBR1) but does not associate with OsRBR2. We created deletion mutants of OsRBR1 and the OsPP2A B” regulatory subunit, the further pairwise assays revealed that the interaction between the OsRBR1 and OsPP2A B” proteins needs an intact pocket domain of retinoblastoma-related protein and the presence of the EF-hands domains on the regulatory subunit. Computer-assisted analysis predicted the presence of three potential CDK phosphorylation sites in the amino-terminal region of the OsPP2A B” regulatory subunit. The phosphorylation assay of the site-directed mutants, which created according to this prediction, has supported the potential phosphorylation. In vivo and in vitro assays indicated that the site-directed mutation of three phosphorylation sites can affect the phosphorylation of OsPP2A B”regulatory subunit and may affect the PP2A-linked phosphatase activity, but did not affect the binding to OsRBR1 and to the OsPP2A catalytic subunits.